2003
DOI: 10.1038/sj.bmt.1704045
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin, C-reactive protein, and endotoxin after bone marrow transplantation: identification of children at high risk of morbidity and mortality from sepsis

Abstract: Summary:We prospectively evaluated the capacity of serum procalcitonin (PCT), compared with serum levels of Creactive protein (CRP) and endotoxin, to identify children at high risk for mortality from sepsis after BMT. Of 47 pediatric bone marrow transplantation patients studied, 22 had an uneventful course post-transplant (Group 1), 17 survived at least one septic event (Group 2), and eight died from multiorgan failure (MOF) following septic shock (Group 3). Median concentrations of PCT over the course of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 29 publications
2
26
2
9
Order By: Relevance
“…Regarding to the kinetics of this marker, in resting neutrophils, CD64 is expressed at very low levels; upon neutrophil activation it However, our group performed a systematic review and meta-analysis about the use of neutrophil CD64 as a marker for bacterial infection and we found that the included studies showed a low methodological quality [18] [12]. We measured the methodological quality with the 25-item criteria developed by the STARD committee [21,22] [18,19]. According to that, one study can score from zero to 25 points, and in our previous meta-analysis, we showed that the 13 included studies had a total score for the STARD checklist that ranged from 9 to 16 points.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to the kinetics of this marker, in resting neutrophils, CD64 is expressed at very low levels; upon neutrophil activation it However, our group performed a systematic review and meta-analysis about the use of neutrophil CD64 as a marker for bacterial infection and we found that the included studies showed a low methodological quality [18] [12]. We measured the methodological quality with the 25-item criteria developed by the STARD committee [21,22] [18,19]. According to that, one study can score from zero to 25 points, and in our previous meta-analysis, we showed that the 13 included studies had a total score for the STARD checklist that ranged from 9 to 16 points.…”
Section: Discussionmentioning
confidence: 99%
“…This observation signifies that PCT levels between 0.5 and 2 ng/ml may be an indicator of serious and life-threatening conditions in febrile neutropenic patients. Sauer et al [46] showed that PCT levels were higher in children with sepsis after bone marrow transplantation when compared to non-septic patients. Children developing septic shock and subsequent MOF had higher PCT values when compared to those with sepsis, and PCT levels were also higher in patients with severe sepsis than in those with sepsis without organ failure.…”
Section: Relationship Between Pct the Severity Of Sepsis And Outcomementioning
confidence: 98%
“…Pihusch et al [28] documented elevated levels of CRP, PCT, and IL-6 in patients who died from transplantrelated complications compared with patients surviving after hematopoietic stem cell transplantation. Sauer et al [46] described higher PCT and CRP levels in non-survivors compared to survivors in children after bone marrow transplantation and sepsis. von Lilienfeld-Toal et al [48] reported a rise in PCT levels shortly before death in patients with febrile episodes and hematological malignancy.…”
Section: Relationship Between Pct the Severity Of Sepsis And Outcomementioning
confidence: 98%
“…Blijlevens et al 6 observed that PCT was of little value in discriminating infections from other inflammatory complications that occurred following allogeneic HSCT. Recently, Sauer et al 7 published a prospective evaluation of capability of serum PCT compared with CRP to identify children with a high risk of mortality from sepsis after HSCT. They concluded that median concentrations of PCT, in contrast to serum CRP and endotoxin, correlated with the severity of sepsis and provided useful prognostic information during septic episodes.…”
Section: Introductionmentioning
confidence: 99%